The relationship of ectoparasite prevalence to the capturing season, locality and species of the murin rodent hosts in Iran - Kordiyeh Hamidi; Leila Nourani; Gholamhossein Moravvej (Persian Journal of Acarology)
The role of rodents in transmission of different parasitic infections, has been well documented. The objective of this study was to determine the relationship between capturing season and rodent habitat with ectoparasites prevalence in the murin rodents from northeast of Iran. Furthermore the host species-related effects on ectoparasitic prevalence were studied.